VIOLATION OF THE RIGHT TO PRIVACY ON THE INTERNET PORTALS IN SERBIA: CASE STUDIES OF PORTALS ESPRESO AND B92 - Grigorov, Aleksandra (CM: Communication and Media ISSN 2466-541X; 2466-5452 (Online), 2021)
This study analyses the characteristics and possibilities of protection of privacy rights on the Internet portals in the Republic of Serbia. The article examines the relationship between these rights and the right to freedom of expression. In accordance with that, the article presented the self-regulatory documents of the Republic of Serbia concerning the media, that serve as the ethical standard of journalists' conduct: The Journalist's Code of Ethics from 2006 and The Guidelines for the Application of The Journalist's Code of Ethics in Online Environment from 2016, the honoring of which is under the jurisdiction of The Press Council. The research is based on the analysis of cases where the privacy rights, dignity and integrity of persons were violated and it includes comparative research of the media reporting on two portals (Espreso and B92) during two separate periods of monitoring the compliance with the The Journalist's Code and The Guidelines in Online Environment. The first monitoring was conducted in cooperation with the Press Council in the period from October 1st to November 30th 2017, while the repeated independent monitoring was conducted in the period from March 1st to March 31 2018, in order to determine whether there had been an improvement on both portals. The monitoring showed that there are violations of privacy rights on both portals, most often in the 'Chronicle' section. The privacy of the victims is violated more frequently than that of the suspects. Also, despite there being a clear reference in The Code about the need of protecting the identity of minors, there have been multiple violations of children's right to privacy, especially in the 'Chronicle' section.